8x-7(x+5)=2x-3

Simple and best practice solution for 8x-7(x+5)=2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-7(x+5)=2x-3 equation:



8x-7(x+5)=2x-3
We move all terms to the left:
8x-7(x+5)-(2x-3)=0
We multiply parentheses
8x-7x-(2x-3)-35=0
We get rid of parentheses
8x-7x-2x+3-35=0
We add all the numbers together, and all the variables
-1x-32=0
We move all terms containing x to the left, all other terms to the right
-x=32
x=32/-1
x=-32

See similar equations:

| 8x-19=3x+61 | | -5x=-30+5x | | (X+3)(x-6)=x^-39 | | 2×(x-10)=x | | (X+3)(x-6)=x2-39 | | 6x-8=4x-34 | | x+((2x-1)/2)+8=0 | | (r−4)2(r+8)=0. | | 14.9=8.6=0.9m | | x+(2x-1)/2+8=0 | | ,-8+x=-10 | | 27=x/6+5 | | 6(4x+5)+1=24x+31 | | 5x-11+3x=4+8x-15 | | 14a=2,968 | | -11=7x2x | | -3(2-m)=6 | | 4​(5x-15​)=20​(x-15) | | x-5/3+5/3=-x/8 | | 39x+18=39x+54 | | -4x+3x=3+2x | | 17y=72+9y | | 10f+2=6f+7 | | 41=8-v | | 47=x+28 | | -6x+9-4(x-1)=-(5x-3)-4x+4 | | 1(3x-4)=11 | | (3−2g)(7−g)=0. | | 10w+15+10w=3w+4 | | 3(4+1)-17=2(3c+2)-3c | | 1(2x-4)=11 | | 62d=3.1 |

Equations solver categories